Use of Emergency Medical Services and Timely Treatment Among Ischemic Stroke: Findings From the China Stroke Center Alliance. Issue 4 (April 2019) - Gu, Hong-Qiu; Rao, Zhen-Zhen; Yang, Xin; Wang, Chun-Juan; Zhao, Xing-Quan; Wang, Yi-Long; Liu, Li-Ping; Wang, Cai-Yun; Liu, Chelsea; Li, Hao; Li, Zi-Xiao; Xiao, Rui-Ping; et al.
Abstract : Background and Purpose—: Emergency medical services (EMSs) are critical for early treatment of patients with ischemic stroke, yet data on EMS utilization and its association with timely treatment in China are still limited. Methods—: We examined data from the Chinese Stroke Center Alliance for patients with ischemic stroke from June 2015 to June 2018. Absolute standardized difference was used for covariates' balance assessments. We used multivariable logistic models with the generalized estimating equations to account for intrahospital clustering in identifying demographic and clinical factors associated with EMS use as well as in evaluating the association of EMS use with timely treatment. Results—: Of the 560 447 patients with ischemic stroke analyzed, only 69 841 (12.5%) were transported by EMS. Multivariable-adjusted results indicated that those with younger age, lower levels of education, less insurance coverage, lower income, lower stroke severity, hypertension, diabetes mellitus, and peripheral vascular disease were less likely to use EMS. However, a history of cardiovascular diseases was associated with increased EMS usage. Compared with self-transport, EMS transport was associated with significantly shorter onset-to-door time, door-to-needle time (if prenotification was sent), earlier arrival (adjusted odds ratio [95% CIs] were 2.07 [1.95–2.20] for onset-to-door time ⩽2 hours, 2.32 [2.18–2.47] for onset-to-door time ⩽3.5 hours), and more rapid treatment (2.96 [2.88–3.05] for IV-tPA [intravenous recombinant tissue-type plasminogen activator] in eligible patients, 1.70 [1.62–1.77] for treatment with IV-tPA by 3 hours if onset-to-door time ⩽2 hours, and 1.76 [1.70–1.83] for treatment with IV-tPA by 4.5 hours if onset-to-door time ⩽3.5 hours). Conclusions—: Although EMS transportation is associated with substantial reductions in prehospital delay and improved likelihood of early arrival and timely treatment, rate of utilization is currently low among Chinese patients with ischemic stroke. Developing an efficient EMS system and promoting culture-adapted education efforts are necessary for improving EMS activation. Abstract : Supplemental Digital Content is available in the text.